Subnational purchasing power of parity in OECD countries Estimates based on the Balassa-Samuelson hypothesis - Costa, Alex (OECD Regional Development Working Papers, 2019)
Due to the lack of Purchasing Power Parities (PPPs) at regional level, regional Gross Domestic Product (GDP) figures have been traditionally adjusted using national PPPs. The simplifying assumption that all regions of a country have the same cost of living, and implicitly that there are no regional differences in prices, might lead to regional GDP figures (adjusted for national PPPs) that are biased and might limit the design and implementation of regional policies. This paper tries to overcome this problem by estimating PPPs at subnational level (TL2 regions) for OECD countries through a new method which uses publicly available data and is based on the Balassa-Samuelson hypothesis